Single phase ac motor control using CPLD / Muhamad Yusri Muhamad Idris - Muhamad Idris, Muhamad Yusri (2005)
This project involves the design, development and operation of single phase AC motor using XILINX. The output voltage is controlled using well known Pulse Width Modulation (PWM) technique. The objective of this project is to regulate the output of AC motor (speed)) using Insulated Gate Bipolar Transistor (IGBT). The design is based on XILINX chip XC95108 Complex Programmable Logic Device (CPLD) that acts as a controller to control the switching of IGBT and modulate the PWM signal externally. A comparison was made between the experimental results obtained and the simulations results from PSpice.